Disease Burden of Total and Early-Onset Colorectal Cancer in China from 1990 to 2019 and Predictions of Cancer Incidence and Mortality - Shao B; Zhu M; Shen K; Luo L; Du P; Li J; Xu J; Deng Y; Lin N; Wu J; Hu W (Clinical Epidemiology, 2023)
Bule Shao,1,2,* Mengjia Zhu,1,* Kai Shen,1,2 Liang Luo,1,2 Ping Du,1,2 Jun Li,1,2 Jing Xu,3 Yanyong Deng,1,2 Ne Lin,1,2 Jiaguo Wu,1,2 Weiling Hu1,2,4 1Department of Gastroenterology, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 2Institute of Gastroenterology, Zhejiang University, Hangzhou, People’s Republic of China; 3Department of Pathology, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 4Cancer Center, Zhejiang University, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiaguo Wu; Weiling Hu, Email ddwjg@163.com; huweiling@zju.edu.cnBackground: Understanding the temporal trends in the epidemiology of colorectal cancer (CRC) and early-onset CRC (EOCRC) in China is essential for policymakers to develop appropriate strategies to reduce the CRC burden.Methods: The prevalence, incidence, mortality, years of life lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life years (DALYs) of CRC were obtained from the Global Burden of Disease (GBD) Study 2019. The incidence and mortality of CRC over the next 25 years were predicted.Results: From 1990 to 2019, the prevalence, incidence, and mortality of total CRC and EOCRC significantly increased in males, with milder trends in females. In 2019, the number of people living with CRC (or EOCRC) in China was approximately 3.4 (0.59) million, which was over seven (five) times higher than that in 1990. The DALYs, YLDs, and YLLs moderately increased from 1990 to 2019 in both sexes. The age-standardized mortality rate (ASMR) for females has shown a stable trend in total CRC, and a downward trend in EOCRC since 2000. While the ASMR for males showed increasing trends in total CRC and EOCRC. In 2019, the highest incidence, prevalence, YLDs, YLLs, and DALYs were all observed in the 65 to 69 age group, while the highest mortality was in the 70 to 74. By 2044, the incidence and deaths of CRC are expected to reach 1310 thousand and 484 thousand, respectively. For EOCRC, the incidence will peak at about 101 thousand around 2034, and the mortality will continuously decrease to a nadir at about 18 thousand around 2044.Conclusion: Although the age-standardized incidence and mortality of total CRC and EOCRC in China will reach a plateau, the number of incident cases and deaths of CRC have been increasing in the last three decades and will continue to increase in the next 25 years.Graphical Abstract: Keywords: early-onset colorectal cancer, prevalence, incidence, mortality, disability-adjusted life years, age-period-cohort analysis